DEVELOPMENT AND RESEARCH OF CONTROL DEVICE OF RIGIDITY OF THREADS BASED ON INDIRECT MEASUREMENTS - Боярчук, Владимир Петрович; Тонконогий, Владимир Михайлович (Eastern-European Journal of Enterprise Technologies, 2010)
The questions of development and laboratory research of control device of inflexibility size of textile filaments of indirect measurement are examined.